Analgesic Effects of Preincision Ketamine on Postspinal Caesarean Delivery in Uganda’s Tertiary Hospital: A Randomized Clinical Trial - Richard Mwase; Tonny Stone Luggya; John Mark Kasumba; Humphrey Wanzira; Andrew Kintu; Joesph V. B. Tindimwebwa; Daniel Obua (Anesthesiology Research and Practice)
Background. Good postoperative analgesic management improves maternal satisfaction and care of the neonate. Postoperative pain management is a challenge in Mulago Hospital, yet ketamine is accessible and has proven benefit. We determined ketamine’s postoperative analgesic effects. Materials and Methods. We did an RCT among consenting parturients that were randomized to receive either intravenous ketamine (0.25 mg/kg) or placebo after spinal anesthetic. Pain was assessed every 30 mins up to 24 hours postoperatively using the numerical rating scale. The first complaint of pain requiring treatment was noted as “time to first breakthrough pain.” Results. We screened 100 patients and recruited 88 that were randomized into two arms of 44 patients that received either ketamine or placebo. Ketamine group had 30-minute longer time to first breakthrough pain and lower 24-hour pain scores. Postoperative diclofenac consumption was lesser in the ketamine group compared to placebo and Kaplan-Meier graphs showed a higher probability of experiencing breakthrough pain earlier in the placebo group. Conclusion. Preincision intravenous ketamine (0.25 mg/kg) offered 30-minute prolongation to postoperative analgesia requirement with reduced 24-hour pain scores. We recommend larger studies to explore this benefit. This trial is registered with Pan African Clinical Trial Registry number PACTR201404000807178.